FACTORS INFLUENCING STUDENTS’ CHOICE OF LEARNING FORMATS - Zokhidov Samandar Iskandar ugli (Prospects for innovative technologies in science and education, 2025)
The rapid expansion of distance and technology-enhanced education has created new learning opportunities while simultaneously requiring a re-evaluation of the psychological, social, and organizational factors that guide students’ educational choices. The selection of a learning format - whether traditional face-to-face, fully online, or blended - depends on how students perceive their personal needs, learning goals, and the resources available to them. The value system of learners, their motivation, attitudes toward learning, and self-regulatory capacities play a central role in this decision-making process. This article examines the psychological factors, value orientations, and contextual influences that shape students’ preferences regarding learning formats in modern higher education.